Guidelines for Strengthening Collaborative Networks in local Governance - Chinnasri, Walaiporn (Local Administration Journal, 2025)
This research article aims to: (1) examine strategies and approaches for strengthening collaborative networks in local government administration; and (2) develop and evaluate guidelines for enhancing collaboration-based governance at the local level. A qualitative research methodology was employed, utilizing in-depth interviews and small group discussions. The study involved 60 key informants from different sectors in three case areas: Na Sam Phan Subdistrict Administrative Organizations in Phetchaburi Province, Bang Duea Subdistrict Municipality in Pathum Thani Province, and Mae Hong Son Provincial Administrative Organization. The study found that informal and voluntary forms of collaboration were most common. These partnerships were primarily driven by government policies and a lack of administrative resources, which limited the capacity of local governments to provide public services independently. To develop effective collaborative models, the study recommends establishing strong network partnerships, ensuring adequate budgetary support, maintaining continuity of activities or projects, and fostering leadership to guide collaborative efforts. The findings also highlight that there is no universal formula for managing collaborative networks; success depends on the local context. Nonetheless, the presence of diverse platforms for meetings, discussions, and knowledge exchange—both formal and informal—is essential. Furthermore, implementing evaluation mechanisms is crucial for assessing the effectiveness and impact of collaborative governance efforts.